THE FORMATION AND DEVELOPMENT OF CORPORATE CULTURE OF THE MEDICAL ORGANIZATIONS - O. L. Zadvornaya (Modernizaciâ, Innovaciâ, Razvitie, 2016)
The article is devoted to the problem of formation and development of corporate culture as the main factor of the successful functioning of medical organization in terms of optimization of activity of the health system. Discusses the importance and main directions of development of corporate culture for personal and organizational development. The authors identified features of the corporate culture of healthcare organizations, the approaches, showing the sequence and contents of the main practical activities on the formation, maintenance and development of corporate culture. Emphasized the need for further research and introduction of corporate culture and cultural values in health care organizations. Purpose/ objectives: to Study and evaluate the corporate culture of healthcare organizations to improve institutional management and increase of efficiency activity of medical organizations. Materials and methods: For data collection methods were used: direct observation, interviews, questionnaires. In conducting this study used data from official sources, a literature review, a systematic approach, comparative analysis, historical, sociological, statistical research methods. The results of the study indicate the need for concept development, tools implementation and development of corporate culture in the practice of the medical organizations.Conclusions/Significance: Corporate culture – the system of collectively shared values, symbols, beliefs, standards of behaviour employees of the organization that contributes to the originality and uniqueness of the activities of medical organizations that promote the identification of employees with the organization; Corporate culture is formed with the influence of factors external and internal environment of the organization, solving problems, external adaptation  and internal integration in the environment; Generated and promoted by the corporate culture is an important management tool, creates strong competitive advantage, increases the social responsibility of medical institutions to the society and patients, improves the quality of medical activities; The presence of the corporate culture of the organization, a coherent system of values and behavior models allows us to improve policy development processes, internal communication, unity and team cohesion, to create a single vector of development of human resources to reduce employee turnover in your organization; Medical organizations need the formation of the concept, mechanisms of implementation and development of corporate culture in practice activities; The system of continuous professional education of managerial staff of health must ensure the implementation of educational programs in the field of formation and development of the corporate culture of healthcare organizations.